PERSONAL FACTOR UNDER CONDITIONS OF COOPERATION BETWEEN THE TEACHER AND STUDENTS IN THE CONTEXT OF THE HUMANISTIC PARADIGM - Marianenko, Liana; Poklad, Iryna (PSYCHOLOGICAL JOURNAL, 2019)
The purpose of the article: to investigate the influence of positive or negative personal qualities of the teacher (levels of pedagogical activity and styles of pedagogical communication), which characterize the interaction as an interruption or assistance in the formation of the teacher’s ability, in particular - the teacher’s ability to form cognitive activity of students. Methods of research: theoretical - methods of logical-psychological and historical-psychological analysis, synthesis, comparison, generalization of theoretical and experimental developments of the studied problem in the scientific literature, systematization, and scientific interpretation for generalization of theoretical and methodological foundations of consideration of the personal factor in the conditions of cooperation between the teacher and students in the context of the humanistic paradigm; empirical - conversation, observation, questioning, testing. The obtained results were subjected to quantitative analysis and qualitative interpretation by methods of data grouping with their further generalization. The scientific novelty is that: the article presents the results an empirical study of the influence of positive or negative qualities of a teacher (styles of pedagogical activity and pedagogical communication) on the formation of students’ cognitive activity; it has been established that an individual style of pedagogical communication can be both positive and negative (for example, democratic, liberal, or authoritarian); it is revealed that the distribution of styles of pedagogical communication (positive and negative) occurs due to the difference in the development of pedagogical orientation and the different correlation of positive and negative moral potential of the teacher’s personality; it is proved that the ability of a teacher to cultivate the moral dualities of students a higher rank positive effect on his ability to form students’ cognitive activity than the ability of a teacher to from children’s mental abilities; it was established experimentally that the ability of a teacher to shape students’ cognitive activity influenced: having his own style of pedagogical communication and high self-esteem of his own creative abilities and the following types of teacher behavior are negatively affecting the ability to form children’s cognitive activity: responsibly generous, straight-aggressive, cooperating-conventional and nervously-skeptical. Practical significance: the analysis and interpretation of the scientific heritage of domestic and foreign scientists can significantly expand the perception of the psychological dimensions of the personal factor in terms of cooperation between subjects of the educational space in the context of the humanistic paradigm. Results: the material obtained during the study can be used by teachers at higher educational establishments during lectures, practical and laboratory classes on educational disciplines "General psychology", "Psychology of personality", "Pedagogical and age psychology", etc.